Landscape-Scale Genetic Structure of Wild Rice Zizania latifolia: The Roles of Rivers, Mountains and Fragmentation - Chen, Yuanyuan; Liu, Yang; Fan, Xiangrong; Li, Wei; Liu, Yanling (Frontiers in Ecology and Evolution, 2017)
Wild rice (Zizania latifolia) is an important genetic resource and it has important ecological functions in aquatic ecosystems as well. Here, we used landscape genetics to investigate how the landscape features, including rivers, mountains and habitat fragmentation, affect the genetic connectivity or create dispersal barriers for Z. latifolia. In this report, seventeen populations from the Sanjiang Plain and its surrounding areas were genotyped by ten microsatellite markers. A high genetic differentiation and genetic discontinuity were found among populations within each river investigated, suggesting that the rivers be not acting as corridors for dispersal. Meanwhile, genetic discontinuity was detected from different sides of the Lesser Khingan and its branch, the Qinghei Mountains, demonstrating that gene flow was blocked by the complex topography of mountains. The results that historical gene flow was much higher than the contemporary gene flow might infer that recent habitat fragmentation resulted in decreased gene flow. For all sampled Z. latifolia populations, the result of low level of genetic variation (na = 2.3, HE = 0.328) and high genetic divergence (FST = 0.405, Dest = 0.414 and Øpt = 0.424) was consistent with the decreased gene flow, an inbreeding system and repeated genetic bottlenecks. A conservation strategy for protecting as many populations as possible to maximize genomic representation of the species is proposed. In addition, dredging the watercourses should be carried out to improve habitat stability and to facilitate connectivity among populations.